Regional African stock markets indices - T. Fish; N. Biekpe (South African Journal of Business Management, 2002)
This paper presents an overview of the construction of regional indices for three of the four regions within Africa. The three indices are the EASDEX (for East Africa), the NADEX (for North Africa) and the WADEX (for West Africa). The SADC region has been excluded, as it has recently been concluded as the subject of study, in which the index, the SADIX was constructed (Tyandela, 2001). The weekly market capitalisation data collected for the construction of these indices was further used to construct an All-Africa index. These indices could in future assist investors both locally and internationally to determine the movement of indices as a way of assessing market trends and opportunities for investment on the African continent.
Keywords: 650